Magnetic, Magnetocaloric, and Electric Transport Properties of Sr2FeMoO6–δ Double Perovskites with Different Degrees of Superstructural Ordering. Issue 8 (15th June 2022) - Kalanda, Nikolay; Demyanov, Sergey; Krupa, Mykola; Konoplyuk, Sergiy M.
Abstract : Pressed strontium ferromolybdate (Sr2 FeMoO6−δ ) pellets with different oxygen indices δ and degrees of superstructural ordering (SO) are synthesized by solid‐phase and citrate‐gel methods to study magnetic and electric transport behaviors of this compound. The crystalline structure of the samples is found to demonstrate ordering of the Fe and Mo cations, which increases with increase in δ. The saturation magnetization and the Curie temperature of the samples correlate with the degree of SO. The Banerjee criterion indicates that the compounds studied undergo a second‐order phase transition. The temperature dependence of the isothermal change of entropy in magnetic field is determined by the Maxwell approach. The additional low‐temperature annealing is found to change the sample conductivity of metallic type for semiconducting one and significantly increases the magnetoresistance due to intergrain electron tunneling. Abstract : The Arrott plot construction demonstrates that magnetostructural transition in Sr2 FeMoO6−δ is of second order. Isothermal change of entropy in magnetic field of 10 kOe reaches 1 J kg −1 K −1, characteristic of rare‐earth magnetic materials. The low‐temperature annealing in Ar/O2 stream modifies the conduction mechanism in Sr2 FeMoO6−δ and leads to an increase in magnetoresistance from 21.2% to almost 44%.